(untitled) (Global Journal of Human-Social Science, 2016)
Menstruation also called the menstrual cycle prepares the sexually mature female body for pregnancy each month Menstruation is monthly bleeding that begins in girls around 12 years of age Because bleeding associated with the menstrual cycle happens regularly or periodically it also is referred to as a menstrual period or more simply as a period Some girls get their first menstrual period as young as 9 years of age and others do not begin menstruating until 15 years of age In developing country Menstruation has always been surrounded by different perceptions throughout the world Nowadays there is some openness toward menstruation but differences in attitude still continue between different populations There are differences between countries cultures religions and ethnics groups In many low-income countries women and girls are restricted in mobility and behavior during menstruation due to their impurity during menstruation